Date: Dec 22, 2012 5:32 PM
Author: camgirls@hush.com
Subject: CANTORS NONSENSE S-PROOF !


S-PROOF!


AD(X) = FLIP(D(X)) ASSUMPTION
AD(1) = FLIP(D(1))
AD(2) = FLIP(D(2))
AD(3) = FLIP(D(3))
...
AND SO ON...

===========

THERFORE
AD(1) =/= D(1)
AD(2) =/= D(2)
AD(3) =/= D(3)
...
AND SO ON

===========

THERFORE
AD(1) =/= L(1,1)
AD(2) =/= L(2,2)
AD(3) =/= L(3,3)
...
AND SO ON


===========

THERFORE
AD =/= L(1)
AD =/= L(2)
AD =/= L(3)
...
AND SO ON

AD(X) =/= L(Y,X) CONCLUSION


===========

Herc
--
www.microPROLOG.com